PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI (Survei pada Karyawan Dinas Pendidikan dan Kebudayaan Karanganyar) - Dery Poernama Putra; Alwi Suddin; Suprayitno Suprayitno (Universitas Slamet Riyadi, 2020)
The purpose of this research is to analyse the significance of the influence of leadership and work discipline on employee performances with motivation as a moderating variable. This research use qualitative and quantitative data. Primary and secondary data is used as the sources of data. The population of this research is employees of Department of Education and Culture in Karanganyar. Total sampling technique is used to take the sample of 74 people. The technique of collecting data using questionnares and documentation. The data analysis technique uses instrument test, classic assumption test, multiple linear regression, t test, F test, coefficient of determination, and test the absolute difference value. The results of this study indicate that leadership has a significant effect on employees performances. Work discipline has a significant effect on employees performance. Motivation has a significant effect on employee performance. Motivation does not moderate the influence of leadership on employees performance. Motivation moderates the influence of work discipline on employees performance.